2017
DOI: 10.1002/ppul.23911
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the T‐cell response to RSV infection is altered in infant mice

Abstract: Together, these data suggest that quantitative and qualitative defects exist in the infant T-cell response to RSV but early, local IFN-γ exposure can increase the CD8 RSV-specific T-cell response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
(77 reference statements)
1
15
0
Order By: Relevance
“…Taking into consideration the findings of this work demonstrating that orally administered L. rhamnosus CRL1505 influence the MHC-II expression of the alveolar macrophages during the course of RSV infection, it is tempting to speculate that the immunobiotic intervention would also beneficially modify the adaptive immune response against the viral pathogen in infant mice. In support of this hypothesis, it has been shown that IFN-γ is able to up-regulate MHC-II expression in alveolar macrophages improving their antigen presentation activities ( 55 ). The evaluation of the influence of L. rhamnosus CRL1505 in the adaptive immune response to RSV and the role of alveolar macrophages in this potential beneficial effect is an interesting topic for future research.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Taking into consideration the findings of this work demonstrating that orally administered L. rhamnosus CRL1505 influence the MHC-II expression of the alveolar macrophages during the course of RSV infection, it is tempting to speculate that the immunobiotic intervention would also beneficially modify the adaptive immune response against the viral pathogen in infant mice. In support of this hypothesis, it has been shown that IFN-γ is able to up-regulate MHC-II expression in alveolar macrophages improving their antigen presentation activities ( 55 ). The evaluation of the influence of L. rhamnosus CRL1505 in the adaptive immune response to RSV and the role of alveolar macrophages in this potential beneficial effect is an interesting topic for future research.…”
Section: Discussionmentioning
confidence: 89%
“…The inefficient production of IFN-γ in the respiratory tract during the course of RSV infection with the subsequent impaired activation of alveolar macrophages has been associated with an increase of severe bronchiolitis and pneumonia in neonates and infants ( 34 36 ). In addition, comparative studies of RSV challenge in infant and adult mice demonstrated that in IFN-γ production were associated to the distinct susceptibility of both groups to viral infection ( 36 , 55 ). Adult mice are able to induce the recruitment of CD8 + IFN-γ + and CD4 + IFN-γ + T cells in the lung, which activated alveolar macrophages and promoted an efficient viral clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine concentrations were determined using the Bio-Plex Pro™ Mouse Cytokine 23-plex Assay (BioRad, CA), per manufacturer's protocol. The right lung was harvested and enzyme-digested into a single cell suspension for flow cytometry, as described previously ( 26 , 27 ). Where indicated, BAL cells and lung homogenate were stimulated ex-vivo for intracellular cytokine detection.…”
Section: Methodsmentioning
confidence: 99%
“…The IFN-γ-mediated activation of alveolar macrophages is essential for efficient viral clearance [41]. It was suggested that quantitative and qualitative differences in IFN-γ production could explain the different susceptibility of infant and adult mice to RSV infection [42]. While adult mice accumulate both CD8 + CD44 high IFN-γ + and CD4 + CD44 high IFN-γ + T in the alveolar space after the challenge with RSV, infant mice accumulate mainly CD8 + CD44 high IFN-γ + T cells in lung tissue and airway.…”
Section: Pigrum 040417 Similar To C Pseudodiphteriticum 090104 mentioning
confidence: 99%